Pemberdayaan Masyarakat Desa Kadirejo dalam Meningkatkan Nilai Tambah Porang - Sarlina Palimbong; Karina Bianca Lewerissa (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Porang is a tuber plant that is widely planted in Kadirejo Village, Pabelan, Semarang Regency. Its abundant harvest can make porang prices fall and harm farmers. To increase the added value of porang, the Women Farmers Group (KWT) received training and education on how to process porang so it doesn't cause itching and irritation in the mouth, process it into porang flour so that its shelf life is longer, and process it to make some derivative products from porang flour. Products made from porang flour were pancakes, nuggets and meatballs. The KWT were satisfied with this activity. They received additional useful new knowledge.